Financial crime community pulse, Romania, 2022 - Achim, Monica Violeta (UK Data Service, 2022)
Our data were collected through a ten question questionnaire. The survey was distributed through various online channels and it was carried out in the second trimester of the year 2022. The valid responses of 1,856 Romanians are summarized, in order to capture their tax compliance and tax morale behaviours, perception of corruption, Anti Money Laundering skills and attitudes towards the Know Your Clients procedures, with respect to their age, gender, region, professional status and education. The objective was to reflect the Romanian perspective on financial crimes on various dimensions, in an accurate an up to date manner. The data may be used for various other multivariate data analysis techniques. The aim of this book was to determine the financial crime community pulse in Romania. For this purpose a survey questionnaire was distributed to 1,856 respondents between May 27th - June 6th 2022. The first objective of our book consists in finding the main patterns that characterize the Romanian community, related to the financial crime perception variables (the level of tax compliance, the level of tax morale reflected as the attitude of citizens towards accepting cheating taxes, the perception of corruption level in the Romanian public institutions, the level of skills possessed by citizens to detect the risk of money laundering and the attitude towards asking for information from the bank officers). We find that a majority of 64% from the interviewed citizens have a good and very good level of tax compliance meaning that they have declared that they paid their taxes long before the last deadline (for discount benefits or not only). Regarding their tax morale, we find that a majority of 74% from the Romanian respondents have an active attitude towards accepting cheating taxes (they usually or always receive their receipt and take it); about 13% of respondents have a proactive attitude (if they do not receive their receipt, they ask for it) while another 13% of our respondents have a passive attitude (if they receive or do not receive their receipt, it doesn't matter). When it comes to corruption, a majority of 66% from the Romanian citizens have declared that they perceived the level of Romanian corruption to be high and very high. Additionally, our results show that a majority of 70% from our citizens have low and very low skills to detect the risk of money laundering in a business; about 25% from the interviewed people have medium skills, while only a percentage of about 5% have high and very high skills to detect suspicious transactions. Regarding the attitude towards asking for information from the bank officers, a majority of about 68% from our citizens have a good attitude towards being asked for information from the bank officers while about 32% have a medium or bad attitude (refuse or hardly provide required information from the bank officers). The second objective of the book is to investigate how the demographic aspects considered in the survey (age, gender, region of living, professional status, and education) are associated with the considered financial crime perception variables. In majority, the demographic variables are found as determinants for financial crime perception, while age is found to hold the highest intensity of impact among all the demographic variables. The results are important for policy makers in order to acknowledge the level in which Romanian citizens perceive the best practices in governance and are aware about the financial crime tendencies, in order to adopt the proper policies that would reduce the level of financial crime in Romania.